2021
DOI: 10.1002/adom.202100683
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Carbon Nitride Macrostructures Derived from Triazine‐Based Cocrystals

Abstract: Graphitic carbon nitrides (CNs) have attracted widespread attention during the last decade, thanks to their potential to address current materials science chal lenges, such as the production of solar fuels by photoelectrochemical means or the catalytic removal of organic pollu tants from water. [1][2][3][4][5] The possibility of tai loring parameters such as charge transfer kinetics, porosity, or energy band positions through approaches including doping, [6] templating, [7] covalent functionalization, [8,9] or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…In order to study this synthetic approach with a wider variety of precursors, thereby showing its applicability to the synthesis of different materials, we replaced melamine with other precursors commonly employed in the preparation of photoactive polymers, namely urea, [48] dicyandiamide (DCD), [49] acetoguanamine (AGA), [50,51] and 2,4,6‐triaminopyrimidine (TAP), [52,53] and we studied the supramolecular self‐assembly behaviour of the resulting mixture. Amongst those monomers, we observed that only TAP was able to form a bulk hydrogel with cyanobenzoic acid, probably owing to the very similar structure and hydrogen‐bonding ability of TAP and MA [46,54] .…”
Section: Resultsmentioning
confidence: 99%
“…In order to study this synthetic approach with a wider variety of precursors, thereby showing its applicability to the synthesis of different materials, we replaced melamine with other precursors commonly employed in the preparation of photoactive polymers, namely urea, [48] dicyandiamide (DCD), [49] acetoguanamine (AGA), [50,51] and 2,4,6‐triaminopyrimidine (TAP), [52,53] and we studied the supramolecular self‐assembly behaviour of the resulting mixture. Amongst those monomers, we observed that only TAP was able to form a bulk hydrogel with cyanobenzoic acid, probably owing to the very similar structure and hydrogen‐bonding ability of TAP and MA [46,54] .…”
Section: Resultsmentioning
confidence: 99%
“…This observation agrees with previous reports, which demonstrate the merit of using supramolecular crystalline materials as precursors to control the structure of the final materials. 22,24,25 The XRD patterns of the CPN x display signals corresponding to an amorphous structure, with a single broad diffraction peak located at 23.1°(Figure S1a). FTIR spectra confirmed the formation of a polyphosphazene network: the C−O−P stretching vibration is visible at 750 cm −1 , and the stretching modes of phosphate groups, ν(P−O−P) 26 and ν(P�O), 27 and heptazine units, ν(C−N/C−N�C), 28 can be seen at 915, 1222, and 2162 cm −1 , respectively (Figure S1b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…By using such supramolecular single crystals as a precursor, the obtained needle-like porous CN nanostructure had an SSA of 185 m 2 ·g −1 , and an increased visible light absorption capacity in range of 450–600 nm. Besides, triazine-based cocrystals composed of two types of molecular units by non-covalent interactions, such as acetoguana-mine-melamine [ 158 ] and terephthalic acid-melamine [ 159 ], were selected as precursors for porous CN via pyrolysis. MOFs have emerged as a new type of precursors for porous carbons-based material and metal/carbon composites [ 160 , 161 ].…”
Section: Pore Modifications Over G -C 3 Nmentioning
confidence: 99%